2019
DOI: 10.1111/jfpp.13973
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, functional and biological properties of degraded polysaccharides from Hylocereus undatu s flowers

Abstract: The present study aimed at investigating the chemical degradation of the polysaccharide (designated as FHRP) isolated from the flowers of Hylocereus undatus (Haw.) Britton et Rose. Two degraded polysaccharides, designated as DFHRP‐1 and DFHRR‐2, were obtained from FHRP by using the Fe2+‐H2O2 degradation method. Physicochemical characterization showed that Fe2+‐H2O2 degradation could effectively decrease the molecular weight of FHRP, but did not significantly change chemical composition and monosaccharide compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…WHC is an important functional indicator, which can reflect the amount of water absorbed and held by the hydrated samples [44]. As shown in Figure 3h, the WHC of LSEP was 2.10 g/g.…”
Section: Water Holding Capacity (Whc) and Oil Holding Capacity (Ohc)mentioning
confidence: 94%
See 1 more Smart Citation
“…WHC is an important functional indicator, which can reflect the amount of water absorbed and held by the hydrated samples [44]. As shown in Figure 3h, the WHC of LSEP was 2.10 g/g.…”
Section: Water Holding Capacity (Whc) and Oil Holding Capacity (Ohc)mentioning
confidence: 94%
“…The OHC of LSEP was measured according to the methods reported by Zhao et al [44]. Briefly, 0.1 g of LSEP was mixed with 10 mL of medium-chain triglycerides (MCTs) in a 25 mL tube.…”
Section: Scanning Electron Microscopy Analysismentioning
confidence: 99%
“…During H 2 O 2 decolorization, H 2 O 2 hydrolyzes into H + and HO 2 − in solution, with the HO 2 − then oxidizing the chromophore or chromogen of the pigment molecule to achieve decolorization. 139 However, too high a concentration of H 2 O 2 may result in degradation of the polysaccharides. Macroporous resin adsorption can be used to simultaneously remove proteins and pigments from polysaccharides.…”
Section: Reviewmentioning
confidence: 99%
“…The well-known approach employing hydrogen peroxide (H 2 O 2 , a strong oxidant) has been increasingly applied to degrade various polysaccharides, due to its strong oxidation ability and environmental-friendly characteristics. Several highly reactive free radicals, such as hydroxyl radical ( • OH), singlet oxygen ( 1 O 2 ), and superoxide radical (O 2 •– ), are capable of degrading polysaccharides and can be activated by various treatments, including metal ions, ascorbic acid, ultrasound, microwave, solution plasma, and ultraviolet (UV) radiation . Furthermore, many studies have reported that free radical-induced structural changes in degraded polysaccharides can efficiently improve their bioactivities, such as the antioxidant activities of degraded Tremella fuciformis, Porphyra yezoensis, Codium cylindricum, and Auricularia auricula polysaccharides; the anti-inflammatory activities of degraded pectin and Hylocereus undatus polysaccharides; ,, the antitumor activities of degraded pectin and glycosaminoglycan polysaccharides; , the probiotic activity of degraded pectin polysaccharide; and the hypoglycemic activity of degraded honeysuckle polysaccharide . Our previous studies confirmed that the degraded polysaccharides prepared from Sargassum fusiforme and Gracilaria lemaneiformis after UV/H 2 O 2 treatment could significantly inhibit the production of pro-inflammatory cytokines and the expression of related genes. , Moreover, it has been reported that vacuolar sugars and sugar-like compounds in plants, including hexoses, sucrose, fructans, and raffinose, can directly scavenge the • OH and • O 2 H radicals produced in cellular membranes .…”
Section: Introductionmentioning
confidence: 99%